UKRAINE AND IRELAND: ARE POST-COLONIAL COUNTRIES, AREN`T THEY? - Баталов, О. А. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
The issue of the membership of Ukraine and Ireland in the post-colonial countries is investigated. The arguments of opponents of the definition of Ukraine as part of the Russian Empire / USSR and Ireland as part of Great Britain as colonies are analyzed: an insufficiently clear definition of empire in modern political science, which allows not at least recognizing the USSR as an empire; absence of official colony status in Ukraine and Ireland; the presence of developed industry in the late USSR, which contradicts colonial status. Each of the arguments is consistently recognized as insufficiently important. The definition of an empire is given, which corresponds to both the British Empire and the Russian / USSR. The typologies of these empires were carried out: Great Britain was recognized as a liberal modern (disciplinary) empire, and the Russian Empire / USSR as an autocratic / authoritarian modern (disciplinary) empire. The key differences of these empires are highlighted. Thanks to the definition of a colony as a territory that has sovereignty limited in favor of the metropolis and is an object of specific colonial policy, as well as the identification of the types of colonies (colonies that are socioculturally close to the metropolis, colonies that are socioculturally different from the metropolis, internal colonies), it is proved that Ukraine as part of the Russian Empire/USSR and Ireland as part of Great Britain correspond to such a variety of colonies as territories dependent on the metropolis, populated socioculturally close to the metropolis in settlement, but not identical to it. An attempt was made to compare the colonial policy of Great Britain in relation to Ireland and the Russian Empire / USSR to Ukraine. Despite the difference in these empires, a significant number of parallels were found: the redistribution of resources in favor of a socioculturally distinct metropolis; cultural and linguistic colonization policies; the spread of specific self-identification of the population («Soviet person» and «British»); resettlement of residents of the metropolis in the colony; the emergence of famine as a result of the colonial policy (Irish potato famine of 1845-1849 and the Holodomor of 1932-1933 in Ukraine). The similarity (goal, struggle methodology, etc.) between the national liberation movements of Ireland (Irish Republican Brotherhood, Irish Republican Army) and Ukraine (Organization of Ukrainian Nationalists, Ukrainian Insurgent Army) is analyzed. As a conclusion, an affirmative answer was provided to the question posed in the title of the article – yes, at this point in time Ukraine is a post-colonial country, and Ireland has been such for at least the first decades after independence.